Analisis Perencanaan Pajak Melalui Metode Penyusutan Untuk Menghitung PPh Pasal 17 Perusahaan Jasa Konstruksi Sebagai Upaya Meminimalkan Beban Pajak Pada PT. Bisma Indo Raya Surabaya Tahun 2022 - Ratna Handayani; Khasanah Sahara; Imarotus Suaidah (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to analyze tax planning using the depreciation method to calculate corporate income tax article 17 as an effort to minimize the tax burden. The data analysis technique used in the research is quantitative descriptive. The data source used in this research is primary data. This research was conducted at PT. Bisma Indo Raya which is located on Jl. East Gayungsari No.16 Surabaya (Behind the PKB Building). The results of this discussion show that the total profit before tax before tax planning from depreciation is Rp. 1,030,470,668, with corporate income tax article 17 amounting to Rp. 226,703,547, resulting in a profit after tax of Rp. 803,767,121. While the calculation of profit after tax planning because there is a correction of depreciation costs using the straight line method, the total profit before tax after tax planning from straight line method depreciation is Rp. 609,820,542 with corporate income tax article 17 of the company amounting to Rp. 134,158,319, so obtained profit after tax amounting to Rp. 475,652,223. Calculating the profit after planning tax due to correction of depreciation costs using the declining balance method, the total profit before tax after tax planning from depreciation is Rp. 486,588,810 with corporate income tax article 17 of Rp. 107,049539, so that the profit after tax is Rp. 379,539,272. So the difference in efficiency of paying income tax if using the straight line depreciation method is Rp. 92,545,228, whereas if using the decreasing balance depreciation method it is Rp. 119,654,009. So the declining balance is smore effective to use because it can provide greater tax reduction efficiency to the company.